Transforming Saltbush: Science, Mobility, and Metaphor in the Remaking of Intercolonial Worlds - Frawley, Jodi; Goodall, Heather (Conservation and society, 2013)
The movement of exotic biota into native ecosystems are central to debates about the acclimatisation of plants in the settler colonies of the nineteenth century. For example, plants like lucerne from Europe and sudan grass from South Africa were transferred to Australia to support pastoral economies. The saltbushAtriplexspp. is an anomaly—it too, eventually, became the subject of acclimatisation within its native Australia because it was also deemed useful to the pastoralists of arid and semi-arid New South Wales. When settlers first came to this part of Australia, however, initial perceptions were that the plants were useless. We trace this transformation from the desert ‘desperation’ plant during early settlement to the ‘precious’ conservation species, from the 1880s, when there were changes in both management strategies and cultural responses to saltbush in Australia. This reconsideration can be seen in scientific assessments and experiments, in the way that it was commoditised by seeds and nursery traders, and in its use as a metaphor in bush poetry to connote a gendered nationalist figure in Saltbush Bill. We argue that while initial settlers were often so optimistic about European management techniques, they had nothing but contempt for indigenous plants. The later impulses to the conservation of natives arose from experiences of bitter failure and despair over attempts to impose European methods, which in turn forced this re-evaluation of Australian species.